Arginine starvation kills tumor cells through aspartate exhaustion and mitochondrial dysfunction. (December 2018) - Cheng, Chun-Ting; Qi, Yue; Wang, Yi-Chang; Chi, Kevin; Chung, Yiyin; Ouyang, Ching; Chen, Yun-Ru; Oh, Myung; Sheng, Xiangpeng; Tang, Yulong; Liu, Yun-Ru; Lin, H.; et al.
Abstract Defective arginine synthesis, due to the silencing ofargininosuccinate synthase 1 (ASS1), is a common metabolic vulnerability in cancer, known as arginine auxotrophy. Understanding how arginine depletion kills arginine-auxotrophic cancer cells will facilitate the development of anti-cancer therapeutic strategies. Here we show that depletion of extracellular arginine in arginine-auxotrophic cancer cells causes mitochondrial distress and transcriptional reprogramming. Mechanistically, arginine starvation induces asparagine synthetase (ASNS), depleting these cancer cells of aspartate, and disrupting their malate-aspartate shuttle. Supplementation of aspartate, depletion of mitochondria, and knockdown of ASNS all protect the arginine-starved cells, establishing the causal effects of aspartate depletion and mitochondrial dysfunction on the arginine starvation-induced cell death. Furthermore, dietary arginine restriction reduced tumor growth in a xenograft model of ASS1-deficient breast cancer. Our data challenge the view that ASNS promotes homeostasis, arguing instead that ASNS-induced aspartate depletion promotes cytotoxicity, which can be exploited for anti-cancer therapies. Chun-Ting Cheng et al. demonstrate that arginine starvation kills arginine-auxotrophic cancer cells by depleting them of aspartate through asparagine synthetase (ASNS) and disrupting their mitochondrial metabolism. This study presents ASNS-induced aspartate depletion as an anti-cancer therapeutic strategy.